Behaviour of cement binder exposed to semi-immersion in chloride-rich salt solutions and seawater with different RH levels. (August 2022) - Sun, Hongfang; Liu, Shuqin; Yu, Fengjiao; Zhang, Xiaogang; Wu, Chuangzhou; Xing, Feng; Ren, Jie
Abstract: Chloride-rich environments including seawater and de-icing salt solutions may lead to severe physical damage to cementitious materials, especially considering the special service environment such as semi-immersion exposure for some concrete structures. The physical degradation behaviour of cement mortars at three different relative humidity (RH) levels was investigated based on changes in physical appearances, dynamic elastic modulus and microstructural analysis. Experimental results showed that RH at 65 ± 5% resulted in obvious salt precipitations on the top region of the tested cement mortar specimens when semi-immersed in NaCl and seawater solutions. Besides, this RH level led to cracks and fractures of specimens with exposure to MgCl2 and CaCl2 solutions, which are closely related to the formation of expansive products, expressed as 0.4MgCO3 ·5.4 Mg(OH)2 ·MgCl2 ·6H2 O and CaCl2 ·CaCO3 ·nH2 O respectively, as confirmed by the microstructural analysis. Interfacial transition zones within binding matrices and sharp edges of specimens are more likely to suffer from salt precipitations. Corresponding different chloride-induced degradation processes owing to various cations or co-existence of various ions in seawater were also proposed and discussed.